Strategies for Success in the Global Islamic Market - Meutia, Cut (Advances: Jurnal Ekonomi & Bisnis, 2023)
The purpose of this study is to comprehensively examine the dynamics of the global Islamic market, with a focus on Islamic marketing, consumer behavior, branding strategies, innovation in Islamic finance, and challenges and opportunities for businesses. The research design and methodology entail a qualitative approach, utilizing a systematic literature review to synthesize existing knowledge and insights from academic articles, books, reports, and scholarly sources. Findings and discussion reveal the paramount importance of integrating Islamic principles with modern marketing practices, emphasizing ethical conduct, authenticity, and social responsibility to engage Muslim consumers effectively. The implications of the study underscore the necessity for businesses to adopt holistic strategies that align with Islamic values to build trust, credibility, and loyalty among Muslim consumers. This multi-perspective approach acknowledges the diverse needs and preferences of Islamic consumers, highlighting the significance of cultural sensitivity, technological innovation, and corporate social responsibility in navigating the complex and competitive landscape of Islamic markets.